Effects of open dumping site on surrounding air, soil, and water: a case study of Biratnagar metropolitan city - Gautam, Aastha; Malla, Diya; Khatiwada, Aadarsh; Kafley, Ghanashyam; Shah, Sujit Kr; Kafle, Sagar (BIBECHANA, 2024)
Managing solid waste is one of the emerging challenges in urban areas, and open dumping and burning is common practices mostly in developing countries like Nepal. Which affects the overall surroundings. The study has investigated the effects of open dumping and burning in nearby air, soil, and river water in dumping site of Biratnagar metropolitan city. For studying the effects on air, the three samples of air were taken, at center and 100m upstream and downstream to the direction of wind flow. Soil samples were taken at 10m from the dumping site center, at 25m from the first sample and at 60m from the second sample, and the water samples were taken at leachate and 100 m upstream and downstream to the leachate. Soil and water were subjected to the physiochemical test, heavy metals test and microbes test whereas PM 2.5, and PM 10 were tested for air  quality. The results showed that the air from upstream has been seen carrying particulate matter from the dumping site to downstream. Similarly, it is found that the quality of water at leachate and downstream is degraded compared to upstream. The soil quality has been found to have degraded due to the harmful and toxic material of the dumping site. Thus, this study shows that open dumping and burning have affected the nearby air, water, and soil.